The geomorphological situation the archaeological sites in Camalau municipality, Paraíba - Azevedo Netto, Carlos Xavier de (2021)
The physical environment allows us to understand the landscape and the forms, processes of occupation of past groups. From the perspective of Geoarchaeology, the human being apprehends the space according to the use of the physical environment; modifying it with the adaptation and manufacturing processes of instruments and the formation of sites, which implies cultural transformation and transition. The article organizes information on the pre-colonial settlements in Camalaú. The methodology of geoarchaeological characterization, elaboration of GIS, and execution of thematic maps permit us to recognize the occupation strategies, which take into account the landforms and the geographical position in relation to the magnetic North. These choices allow the understanding of pre-colonial occupation strategies in the Cariris Velhos.